Studi Mengenai Brand Awareness Online Marketplace - Gilang Puspita Rini; Etni Marliana (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2020)
Online media is growing rapidly in Indonesia, including in the field of trade. Internet users in Indonesia are increasing from year to year. Information flow, especially through online media, can come from advertisements and word of mouth. Companies that sell in the online market must be able to make their products have brand awareness so that it will influence the purchasing decision process. One study of brand awareness states that one of them is influenced by the effectiveness of advertising and word of mouth. The results of previous studies indicate inconsistencies of research results related to variables that affect brand awareness. This study aims to examine the differences in the results of previous studies that give different results among studies regarding the factors that influence brand awareness. The sample used in this study is internet users in Indonesia who have already made purchase transactions in the online marketplace. After processing data with SPSS, the results are obtained that the effectiveness of advertisements and word of mouth affects brand awareness.